Seismic Response Mitigation of a Long-Span Tower Bridge with Two Types of Constraint System - Li Xu; Qingfei Gao; Junhao Zheng; Chuanhui Ding; Kang Liu (Advances in Civil Engineering)
The stress of the main tower of a cable-stayed bridge depends on the connection type between the tower and deck. In order to study the most suitable longitudinal damping mode for a long-span cable-stayed bridge. In this article, a nonlinear finite element model is established based on a large span concrete cable-stayed bridge with a main span of 680 m. Without considering the influence of the transverse constraint, the damping effect of the elastic connection device and the viscous damper is simulated when the longitudinal seismic load is input. The results show that the stiffness of the main beam is increased by installing the elastic connection device, so the longitudinal drift frequency of the main beam is increased, but the stiffness of the structure is not changed by installing the viscous damper. Both viscous dampers and elastic connection structures can reduce the longitudinal displacement of the beam end, but viscous dampers are more favorable for the stress of the main tower. In terms of damping effect, viscous dampers are more suitable for long-span cable-stayed bridges, but, in terms of economy and parameter control, elastic connection devices have more advantages.